Wound healing: an update. (November 2014) - Zielins, Elizabeth R; Atashroo, David A; Maan, Zeshaan N; Duscher, Dominik; Walmsley, Graham G; , Owen Marecic; Hu, Michael; Senarath-Yapa, Kshemendra; McArdle, Adrian; Tevlin, Ruth; Wearda, Taylor; Paik, Kevin J; et al.
Wounds, both chronic and acute, continue to be a tremendous socioeconomic burden. As such, technologies drawn from many disciplines within science and engineering are constantly being incorporated into innovative wound healing therapies. While many of these therapies are experimental, they have resulted in new insights into the pathophysiology of wound healing, and in turn the development of more specialized treatments for both normal and abnormal wound healing states. Herein, we review some of the emerging technologies that are currently being developed to aid and improve wound healing after cutaneous injury.